Intrauterine growth curve and application in intrauterine growth restriction diagnosis - Tipiani Rodríguez, Oswaldo (2015)
Background: Intrauterine growth restriction (IUGR) increases the risk for perinatal morbidity and mortality. Diagnoses vary according to reference growth curves. In our institution, Lubchenko’s curve is used primarily. Objectives: To build our own intrauterine growth curve (IGC) and compare it with Lubchenko's and Peruvian Ministry of Health’s (MINSA) curves regarding IUGR. Design: Observational, retrospective, comparative study. Setting: Department of Gynecology and Obstetrics,  Obstetrics Critical Care Service, Hospital Nacional Edgardo Rebagliati Martins (HNERM), EsSalud, Lima, Peru. Participants: Neonates. Methods: We reviewed information of mothers and neonates born at HNERM between January 1, 2003, and June 30, 2010. Mothers with only one fetus were included, 24 to 43 weeks of gestation by reliable last menstrual period and/or first trimester ultrasound exam; 29 239 newborns were included. Data was obtained from the hospital’s Fetal surveillance Service data base. An intrauterine growth curve (IUGC) was built and compared with Lubchenko's and MINSA's growth curves by Student t, ANOVA and non-parametric tests. Differences were considered significant when p < 0.05. We used SPSS and Microsoft Excel for data processing. Main outcome measures: Intrauterine fetal growth curve. Results: The IUGC was built and percentiles were significantly higher to both Lubchenco’s and MINSA’s curves. Neonatal weight was influenced by maternal height, pregestational weight, maternal age (ANOVA: F = 3,8; F = 214,7; and, F = 11,2, respectively; p < 0,05), male fetal sex and multiparity (student t; p<0,001). Both MINSA’s and Lubchenco’s growth curves missed diagnosis of a significant percentage of fetuses with perinatal morbidity and mortality proper of IUGR. Conclusions: Intrauterine fetal growth curve built with HNERM patients differed significatively from those of both Lubchenco and MINSA. The latter subdiagnosed a significant percentage of fetuses with IUGR, reason to recommend the use of growth curves built with our hospital population. Conclusions: Intrauterine growth curve built with HNERM patients differed significantly from that of Lubchenko's and MINSA's. The latter underdiagnosed a significant percentage of fetuses with IUGR. Thus we recommend the use of our own curves in our hospitalinfluenced area population.